2021
DOI: 10.3389/fmicb.2021.679808
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Effect of Thymoquinone on Alicyclobacillus acidoterrestris Vegetative Cells, Spores, and Biofilms

Abstract: Alicyclobacillus acidoterrestris (A. acidoterrestris), a spore-forming bacterium, has become a main challenge and concern for the juices and acid beverage industry across the world due to its thermo-acidophilic characteristic. Thymoquinone (TQ) is one of the active components derived from Nigella sativa seeds. The objective of this study was to investigate antibacterial activity and associated molecular mechanism of TQ against A. acidoterrestris vegetative cells, and to evaluate effects of TQ on A. acidoterres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Notably, the observed significant upregulation of sigF suggests that TQ causes the exhaustion of energy resources in bacterial cells; thus, transcriptomic observations were consistent with metabolomic ones. The TQ mechanism of action described in this study is in agreement with previously reported damage to the cytoplasmic membrane ( Fan et al, 2021 ), and a decrease in intracellular ATP concentration ( Wang et al, 2021 ). It is worth noticing that the stability of TQ in bacterial broth was limited and, after 48 h, significantly lowered.…”
Section: Conclusion and Limitations Of The Studysupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the observed significant upregulation of sigF suggests that TQ causes the exhaustion of energy resources in bacterial cells; thus, transcriptomic observations were consistent with metabolomic ones. The TQ mechanism of action described in this study is in agreement with previously reported damage to the cytoplasmic membrane ( Fan et al, 2021 ), and a decrease in intracellular ATP concentration ( Wang et al, 2021 ). It is worth noticing that the stability of TQ in bacterial broth was limited and, after 48 h, significantly lowered.…”
Section: Conclusion and Limitations Of The Studysupporting
confidence: 92%
“…TQ’s antibacterial mechanism of action was studied in several bacterial species other than mycobacteria. It included the inhibition of cell adhesion to the glass slide surface ( Chaieb et al, 2011 ), production of reactive oxygen species ( Goel and Mishra, 2018 ), changes in the cell morphology, damage to the cytoplasmic membrane ( Fan et al, 2021 ), membrane depolarization, and decrease in intracellular ATP concentration ( Wang et al, 2021 ). However, there are no reports about the TQ mode of action in M. tuberculosis .…”
Section: Introductionmentioning
confidence: 99%
“…This effect became more pronounced with higher quercetin concentrations, highlighting the impact on cell membrane permeability further. Fan et al (2021) investigated the impact of thymoquinone on the membrane integrity of A. acidoterrestris using laser scanning confocal microscopy and fluorescent dye PI and found negligible red fluorescence in the control group. However, upon treatment with 1 MIC thymoquinone, a modest amount of red fluorescence was observed, indicating the disruption of membrane integrity in certain cells.…”
Section: Effect Of Quercetin On Membrane Damage Of Alicyclobacillus A...mentioning
confidence: 99%